Public perceptions and attitudes of the national project of bio-big data: A nationwide survey in the Republic of Korea - Yang, Ji Hyun; Kim, Hannah; Lee, Ilhak (Frontiers in Genetics, 2023)
Background: The National Project of Bio-Big Data (NPBBD) is a South Korean bio-big data collection project, expected to include health, genomic, and lifelog data of one million Koreans. The Ethics, Legal and Social Implications study is a parallel study active since 2020. As part of the study, a public survey was conducted to confirm public attitudes towards engagement schemes, such as public committees and web portals for communication between the public and researchers. Methods: An online survey was conducted from March 3–9, 2021, using structured questionnaires addressed to 1,000 adults aged 20–59 years. Results: Several respondents reported a positive attitude towards participation (43.6% “somewhat,” 14.3% “definitely”), whereas approximately one-third (36.5%) reported a neutral attitude. Positive factors that may affect the willingness of the respondents to participate included receiving health information (25.1%), contributing to research on cancer and rare diseases (21.9%), and advancing personalized medicine (21.5%). Conversely, negative factors were mainly associated with concerns regarding the risk of data leakage (22.8%), discrimination (21.1%), lack of information (13.5%), possibility of knowing the risk of being diagnosed with an incurable diseases (12.5%), and possibility of using data in industry (11.3%). In terms of project governance, respondents tended to recognize the importance of public participation in incorporating public opinion into the project design. Conclusions: These results have implications for the participant recruitment process, public engagement strategies, and the scope of user (academics/industry, domestic/overseas) accessibility to the database.